Changes in work and life patterns associated with depressive symptoms during the COVID-19 pandemic: an observational study of health app (CALO mama) users. (22nd February 2021) - Sato, Koryu; Sakata, Ryohei; Murayama, Chiaki; Yamaguchi, Mai; Matsuoka, Yoko; Kondo, Naoki
Abstract : Background: During the COVID-19 pandemic, many people refrained from going out, started working from home (WFH), and suspended work or lost their jobs. This study examines how such pandemic-related changes in work and life patterns were associated with depressive symptoms. Methods: An online survey among participants who use a health app called CALO mama was conducted from 30 April to 8 May 2020 in Japan. Participants consisted of 2846 users (1150 men (mean age=50.3) and 1696 women (mean age=43.0)) who were working prior to the government declaration of a state of emergency (7 April 2020). Their daily steps from 1 January to 13 May 2020 recorded by an accelerometer in their mobile devices were linked to their responses. Depressive symptoms were assessed using the Two-Question Screen. Results: On average, participants took 1143.8 (95% CI −1557.3 to −730.2) fewer weekday steps during the declaration period (from 7 April to 13 May). Depressive symptoms were positively associated with female gender (OR=1.58, 95% CI 1.34 to 1.87), decreased weekday steps (OR=1.22, 95% CI 1.03 to 1.45) and increased working hours (OR=1.73, 95% CI 1.32 to 2.26). Conversely, starting WFH was negatively associated with depressive symptoms (OR=0.83, 95% CI 0.69 to 0.99). Conclusions: Decreased weekday steps during the declaration period were associated with increased odds of depressive symptoms, but WFH may mitigate the risk in the short term. Further studies on the longitudinal effects of WFH on health are needed.